Advances in coral immunity ‘omics in response to disease outbreaks - Nikki Traylor-Knowles; Andrew C. Baker; Kelsey M. Beavers; Neha Garg; Jeffrey R. Guyon; Aine Hawthorn; Nicholas J. MacKnight; Mónica Medina; Laura D. Mydlarz; Esther C. Peters; Julia Marie Stewart; Michael S. Studivan; et al. (Frontiers in Marine Science, 2022)
Coral disease has progressively become one of the most pressing issues affecting coral reef survival. In the last 50 years, several reefs throughout the Caribbean have been severely impacted by increased frequency and intensity of disease outbreaks leading to coral death. A recent example of this is stony coral tissue loss disease which has quickly spread throughout the Caribbean, devastating coral reef ecosystems. Emerging from these disease outbreaks has been a coordinated research response that often integrates ‘omics techniques to better understand the coral immune system. ‘Omics techniques encompass a wide range of technologies used to identify large scale gene, DNA, metabolite, and protein expression. In this review, we discuss what is known about coral immunity and coral disease from an ‘omics perspective. We reflect on the development of biomarkers and discuss ways in which coral disease experiments to test immunity can be improved. Lastly, we consider how existing data can be better leveraged to combat future coral disease outbreaks.